The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/acr.22001
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Women and Men With Recent‐Onset Axial Spondyloarthritis: Results From a Prospective Multicenter French Cohort

Abstract: Objective. To clarify sex differences in early axial spondyloarthritis (SpA). Methods. In total, 475 patients included in the Devenir des Spondylarthropathies Indifférenciées Récentes (Outcome of Recent Undifferentiated Spondylarthropathies) cohort, a prospective multicenter French cohort of patients with early inflammatory back pain suggestive of SpA, and fulfilling the Assessment of SpondyloArthritis international Society (ASAS) classification criteria for axial SpA were studied. The clinical and imaging fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
111
3
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(159 citation statements)
references
References 25 publications
(39 reference statements)
22
111
3
16
Order By: Relevance
“…These studies confirm differences in disease expression between men and women in the diagnosis of nr-axSpA [7,21]. Women with early nr-axSpA clearly have greater disease activity despite fewer radiologic abnormalities compared to men.…”
Section: Characteristics Of Nonradiographic Axial Spasupporting
confidence: 75%
See 2 more Smart Citations
“…These studies confirm differences in disease expression between men and women in the diagnosis of nr-axSpA [7,21]. Women with early nr-axSpA clearly have greater disease activity despite fewer radiologic abnormalities compared to men.…”
Section: Characteristics Of Nonradiographic Axial Spasupporting
confidence: 75%
“…Studies question whether coexistent fibromyalgia may be a confounding factor in assessing disease activity and establishing a diagnosis of axSpA in this female patient population [22,23]. Since clinical features of fibromyalgia and SpA overlap, the clinical arm of the ASAS criteria may lead to over-diagnosis of axSpA in women and the lower specificity of the clinical arm (84 %) compared to the imaging arm (97 %) reflects this difficulty [21]. Further research and evaluation of MRI over disease course is needed to clarify this area of interest.…”
Section: Characteristics Of Nonradiographic Axial Spamentioning
confidence: 99%
See 1 more Smart Citation
“…Female gender is associated with higher BASDAI, fatigue and function scores despite less radiographic and MRI modifications than men. Women with radiographic sacro ileitis have more peripheral involvement [28]. Uveitis is associated with cervical involvement, a preceding history of infection and presence of IBD [29].…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have not uniformly confirmed male predominance in SpA. To clarify sex differences, a cohort of 708 patients with early inflammatory back pain suggestive of axSpA was recruited for a prospective multicenter French study 48 . Among the 475 patients diagnosed with SpA, 50.3% were men and 49.7% women.…”
Section: Kopylov Et Al: the Space Capsule Studymentioning
confidence: 99%